High EVI1 expression is associated with MLL rearrangements and predicts decreased survival in paediatric acute myeloid leukaemia: a report from the children's oncology group. (4th July 2013) - Ho, Phoenix A.; Alonzo, Todd A.; Gerbing, Robert B.; Pollard, Jessica A.; Hirsch, Betsy; Raimondi, Susana C.; Cooper, Todd; Gamis, Alan S.; Meshinchi, Soheil
Summary Ectopic viral integration site‐1 (EVI1) is highly expressed in certain cytogenetic subsets of adult acute myeloid leukaemia (AML), and has been associated with inferior survival. We sought to examine the clinical and biological associations of EVI1high, defined as expression in excess of normal controls, in paediatric AML. EVI1 mRNA expression was measured via quantitative real‐time polymerase chain reaction in diagnostic specimens obtained from 206 patients. Expression levels were correlated with clinical features and outcome. EVI1high was present in 58/206 (28%) patients. MLL rearrangements occurred in 40% of EVI1high patients as opposed to 12% of the EVI1low/absent patients (P < 0·001). No abnormalities of 3q26 were found in EVI1high patients by conventional cytogenetic analysis, nor were cryptic 3q26 abnormalities detected in a subset of patients screened by next‐generation sequencing. French‐American‐British class M7 was enriched in the EVI1high group, accounting for 24% of these patients. EVI1high patients had significantly lower 5‐year overall survival from study entry (51% vs. 68%, P = 0·015). However, in multivariate analysis including other established prognostic markers, EVI1 expression did not retain independent prognostic significance. EVI1 expression is currently being studied in a larger cohort of patients enrolled on subsequent Children's Oncology Group trials, to determine if EVI1high has prognostic value in MLL‐rearranged or intermediate‐risk subsets.